2014
DOI: 10.3189/2014aog66a135
|View full text |Cite
|
Sign up to set email alerts
|

Mountain glaciers of southeast Siberia: current state and changes since the Little Ice Age

Abstract: ). The Kodar glaciers have experienced the largest area shrinkage, while the area loss on Baikalsky ridge was more moderate. Glacier changes are mainly related to regional summer temperature increase (by 1.7-2.68C from 1970 to 2010). There are some differences in glacier response due to different spatial patterns of snow accumulation, local topography (e.g. glacier elevation, slope) and geological activity. The studied glaciers (especially of Kodar ridge) are the most sensitive in Siberia to climate change sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 6 publications
2
18
0
1
Order By: Relevance
“…In addition, more compact glaciers with steeper surface slopes shrank less in absolute terms. These findings match those observed in the earlier studies of East Siberia glaciers [16,19,22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, more compact glaciers with steeper surface slopes shrank less in absolute terms. These findings match those observed in the earlier studies of East Siberia glaciers [16,19,22].…”
Section: Discussionsupporting
confidence: 92%
“…The total area loss of the studied East Sayan glaciers is similar to that obtained in other regions, for example, in the Alps where the overall glacier area reduction from 1850 to 2000 was almost 50% [18]. The data obtained confirm our previous conclusion that the ice area reduction in the region of south East Siberia since the Little Ice Age was among the highest in Eurasia and these glaciers were very sensitive to climate change [16,19]. Probably, the southerly position of the glaciers (e.g., in comparison to north-east Siberia) and their relatively low elevations were among the causes of increased ice loss.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…RGI 4.0 contains 2207 glaciers in this subregion, with a total area of 1803 km 2 (Pfeffer and others, 2014; Table 2). Most studies have found that glaciers retreated during the 20th century in response to higher summer temperatures, with an acceleration of loss in the past three decades (Kadota and Gombo, 2007;Surazakov and others, 2007;Shahgedanova and others, 2010;Zhang and others, 2012;Kamp and others, 2013;Osipov and Osipova, 2014; Table 1). Taken together, these studies have provided a complete glacier inventory for the AM subregion.…”
Section: Previous Researchmentioning
confidence: 99%
“…Our study centres on the Kodar Mountains, the highest massif in the region, which currently hosts over 30 small cirque glaciers (Preobrazhenskiy, 1960;Shahgedanova et al, 2003Shahgedanova et al, , 2011Stokes et al, 2013;Osipov and Osipova, 2014). We collected samples for exposure dating from boulders on moraine complexes in the Chara Depression and in the River Vitim valley (Table 1 .…”
Section: Field Sitesmentioning
confidence: 99%